The South-South Opportunity - Pradhan, Sanjay (2012)
Imagine, just a few years from now, a developing country official who is struggling with a difficult problem: perhaps reintegrating demobilized soldiers back into their communities that have been torn by conflict, or helping the desperately poor climb out of poverty through targeted assistance programs.